Narrative Review: Efforts to Prevent Stunting through the Role of Midwifery during the First 1,000 Days of Life - Dhea Ayunanda; Maria Doresia Sidabungke; Siti Nurjannah; Andre Prantino Depeda; Lita Anggraini (International Journal of Psychology and Health Science, 2025)
Stunting remains one of the major chronic nutritional problems and a serious challenge in Indonesia. This condition not only affects children’s physical growth but also impacts cognitive development, productivity, and the overall quality of human resources in the future. The Government of Indonesia has set a target to reduce the prevalence of stunting through various cross-sectoral programs, ranging from specific nutrition interventions to broader sensitive interventions. This article discusses the causes of stunting, prevention strategies involving the health, education, social, and economic sectors, as well as the role of public policy in supporting these efforts. A review of the literature indicates that reducing stunting requires an integrated approach focused on the First 1,000 Days of Life, improved access to health services, provision of nutritious food, community education, and stronger inter-agency coordination. The findings highlight that the success of stunting prevention depends not only on medical interventions but also on policy synergy, community participation, and long-term political commitment. With appropriate and sustainable strategies, Indonesia has the potential to achieve its stunting reduction targets in line with the Sustainable Development Goals (SDGs) 2030 agenda.